System design of a microstrip antenna by dimension and substrates optimization - Africa, Aaron Don M.; Pasia, Samuel Alexander; Sy, Jereme Adriane (Institute of Advanced Engineering and Science, 2024)
The microstrip antennas matured and improved over the last 25 years. Throughout these years, the limitations, and specifications of the said antennas have been overcome and significantly improved. Known to be lowprofile, suitable for mobile, and lightweight, these microstrip antennas are the focus of this research. In this paper, the researchers designed a microstrip antenna with varying lengths and substrates. They tested the changes and the effects in microstrip antennas of different lengths, along with altering substrates. To verify the differences, the researchers compared the performance parameters maximum gain (dBi), minimum gain (dBi), and S11 graph on each tested length and changed substrate. The rough set theory was used to determine the optimal design via MATLAB. From there, the researchers analyzed the results gathered and drew their respective conclusions. Additionally, they saw and compared each data result to know what antenna has the best performance parameters. From the results, a change in the dimension will result in a decrease in the said performance parameters. Furthermore, the change in substrate thickness also diminishes these changes.